2010
DOI: 10.1152/ajpheart.00074.2010
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological studies of transgenic long QT type 1 and type 2 rabbits reveal genotype-specific differences in ventricular refractoriness and His conduction

Abstract: studies of transgenic long QT type 1 and type 2 rabbits reveal genotype-specific differences in ventricular refractoriness and His conduction. Am J Physiol Heart Circ Physiol 299: H643-H655, 2010. First published June 25, 2010; doi:10.1152/ajpheart.00074.2010.-We have generated transgenic rabbits lacking cardiac slow delayed-rectifier K ϩ current [IKs; long QT syndrome type 1 (LQT1)] or rapidly activating delayedrectifier K ϩ current [IKr; long QT syndrome type 2 (LQT2)]. Rabbits with either genotype have prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
4
29
1
Order By: Relevance
“…Using this method, we demonstrated that at baseline, spatial APD dispersion did not differ significantly between LQT1 and LMC rabbits as also shown in vivo (ventricular refractory periods) and ex vivo in previous studies in LQT1 rabbits [16], [25], [28] – albeit there was a non-significant trend towards an even less pronounced APD dispersion in LQT1. The lack of differences in APD dispersion at baseline matches data of electrophysiological studies in LQT1 patients, who similarly did not yield greater APD dispersion compared to a healthy control group [34].…”
Section: Discussionsupporting
confidence: 75%
“…Using this method, we demonstrated that at baseline, spatial APD dispersion did not differ significantly between LQT1 and LMC rabbits as also shown in vivo (ventricular refractory periods) and ex vivo in previous studies in LQT1 rabbits [16], [25], [28] – albeit there was a non-significant trend towards an even less pronounced APD dispersion in LQT1. The lack of differences in APD dispersion at baseline matches data of electrophysiological studies in LQT1 patients, who similarly did not yield greater APD dispersion compared to a healthy control group [34].…”
Section: Discussionsupporting
confidence: 75%
“…Young (aged 5-7 mo, n ϭ 6) and old (aged 3.5-5.5 yr, n ϭ 8) female NZW rabbits were subjected to transvenous electrophysiological studies (EPS) as described (41). Briefly, rabbits were anesthetized with ketamine/xylazine (25 mg·kg Ϫ1 ·3.75 mg Ϫ1 ·kg Ϫ1 im) and buprenorphine (0.03 mg/kg sq), intubated, and ventilated with isoflurane (1-2%, FI O 2 0.5).…”
Section: In Vivo Electrophysiological Studiesmentioning
confidence: 99%
“…EPS were performed at a stimulation cycle length (CL) of 200 and 240 ms. The following electrophysiological parameters were analyzed as previously described (41): sinus node recovery time (SNRT) was evaluated at pacing drive rates of 200 and 240 ms after 200 beats, and the heart rate-corrected SNRT (SNRT Ϫ sinus CL) was calculated. Atrium-to-His (AH) and His-to-ventricle (HV) intervals that reflect conduction from the atrium to the proximal His bundle (AH) and from the His bundle via Purkinje fibers to the ventricle (HV) were measured.…”
Section: In Vivo Electrophysiological Studiesmentioning
confidence: 99%
“…The protocol was modified from a previously published protocol from our laboratory (45). Rabbits were anesthetized and monitored as described for MI induction.…”
Section: Minimally Invasive In Vivo Electrophysiological Studymentioning
confidence: 99%
“…Atrium to His (AH) and His to ventricle (HV) intervals were measured. Programmed ventricular stimulation was performed with one, two, and three extra stimuli in apical and basal positions to examine inducibility of monomorphic ventricular tachycardia or ventricular fibrillation (45). We strictly defined all ventricular tachycardia or ventricular fibrillation as sustained ventricular arrhythmias requiring cardioversion or defibrillation respectively.…”
Section: Minimally Invasive In Vivo Electrophysiological Studymentioning
confidence: 99%